Hubungan Konsumsi Fast Food dengan Obesitas pada Remaja di SMA Negeri 5 Makassar - Nurfaidah; Asikin, Abdul Malik; Alimuddin, Hadijah; Alam, Nur (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2025)
Adolescent obesity is increasing in Indonesia due to lifestyle changes, low physical activity, and high consumption of fast food influenced by social media promotions. This study aims to analyze the relationship between fast food consumption habits and physical activity with obesity among adolescents at SMA Negeri 5 Makassar. This study employs a cross-sectional design with a descriptive-analytical method. The sample consists of 87 students selected through proportional random sampling. Data were obtained through anthropometric measurements and questionnaires on fast food consumption and physical activity, then analyzed using bivariate statistical tests with SPSS version 12 at a 95% confidence level (α=0.05). The results showed that out of 87 respondents, 12 students (13.8%) were obese, while 75 students (86.2%) were not obese. Most respondents had a high fast food consumption pattern (65.5%), and statistical analysis indicated a significant relationship between fast food consumption frequency and obesity (p<0.05). Moreover, low physical activity was also correlated with an increased prevalence of obesity. The conclusion of this study is that high fast food consumption and low physical activity contribute to obesity among adolescents. These findings highlight the importance of nutritional education and the promotion of a healthy lifestyle among adolescents as a preventive measure against obesity. Key words: Obesity, Adolescents, Fast Food